Software for computer control 1982 : proceedings of the Third IFAC/IFIP Symposium, Madrid, Spain, 5-8 October 1982 - Ferrate, Gabriel A., 1932-; Puente, E. A. (IFAC proceedings series., 1983)
Software for Computer Control 1982 covers the proceedings of the Third IFAC/IFIP Symposium. The book discusses the state of software development for digital computer applications for science and control. With a total of 73 papers, the book covers topics such as real-time language and operating systems; man-machine communication software; software for robots; software for distributed control systems; C.A.D. of digital computer controls systems; algorithms for digital computer control; control software engineering and management; and industrial applications. Computer scientists, engineers, and I.